THE ANALYSIS OF REGISTER USED IN FIVE SELECTED BEAUTY VLOGGERS VIDEOS ON YOUTUBE - Fransiska Yuanita; Muhammad Bahri Arifin; Setya Ariani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This research aimed to find out the types of beauty register, the linguistic forms, and the language functions in the five selected beauty vloggers videos on YouTube. The design of this research was a descriptive qualitative. The data concerned were words, compound words, and phrases taken from two different sources: ten videos’ transcripts and ten videos. Data collection was performed through watching the ten beauty vloggers videos, reading the ten videos’ transcripts, and taking notes of the needed data. Data analysis was conducted through data reduction, data display, and conclusion drawing. There were three results found in this research. First, the types of register identified in the ten beauty vloggers videos were casual and consultative. Second, the linguistic forms of each beauty register found were categorized into three divisions: (1) words, compound words, and phrases as grammatical unit; (2) noun, verb, and adjective as grammatical category; and (3) object and predicate as grammatical functions. Third, the language functions contained within all the beauty registers found were identified as ideational and textual. As the conclusion, the use of register may differ following to the social setting where the speaker is involved. Keywords: linguistic, register, language function, beauty vlogger